2005
DOI: 10.1111/j.1464-410x.2005.05464.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde ureteroscopy for distal ureteric stone removal in children

Abstract: OBJECTIVETo compare the efficacy and safety of ureteroscopy plus intracorporeal lithotripsy (ULT) with extracorporeal shock wave lithotripsy (ESWL) for treating distal ureteric calculi in childhood, as such stones are commonly treated by ESWL as the first option in adults but there is no agreement on the method of treating them in children. PATIENTS AND METHODSFrom July 2002 to July 2003, children presenting with ureteric stones were consecutively randomized for treatment using ULT or ESWL. The two groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 26 publications
(59 reference statements)
0
33
1
1
Order By: Relevance
“…Dominicis et al [6] compared the efficacy and safety of ureteroscopy with extracorporeal shock wave lithotripsy (ESWL) for treating distal ureteric calculi. In all 17 children underwent ureteroscopy and 14 children had ESWL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominicis et al [6] compared the efficacy and safety of ureteroscopy with extracorporeal shock wave lithotripsy (ESWL) for treating distal ureteric calculi. In all 17 children underwent ureteroscopy and 14 children had ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for stent (1) Stone migration (2) Hematuria (1) Renal colic (1) Dominicis et al [6] 17 (17) placement has traditionally been to reduce the chances of stricture formation, postoperative pain, and acute pyelonephritis. However ureteral stents themselves are known to be responsible for significant pain and bladder spasms.…”
Section: Discussionmentioning
confidence: 99%
“…In SWL group, the stone free rate was 43% (6 of 14) after the first session, 64% (9 of 14) after the second session. The five patients of SWL group underwent successful ureteroscopy (11). These studies show that these two treatment modalities have almost the same clinical success with SWL group having more auxially measures.…”
Section: Discussionmentioning
confidence: 53%
“…Large series using primarily rigid ureteroscopes with electrohydraulic, ultrasonic and holmium laser lithotripsy for distal ureteral stones have reported stone-free rates of 86-100% with low complication rates [11,12] . In a randomized study comparing URS and ESWL as primary therapies for distal ureteral stones in 31 children, De Dominicis et al [13] found significantly better stone-free rates in URS-treated patients. In our series of successful URS in children ^ 12 years, the overall complication rate was only 3.8%.…”
Section: Discussionmentioning
confidence: 99%